Pesantren dalam Sistem Pendidikan Nasional: Analisis UU Pesantren 2019 terhadap Pendidikan Diniyyah Formal dan Pendidikan Mu’adalah di Indonesia - Akhmad Afnan Fajarudin; Ahmad Ihwanul Muttaqin (Kitabaca : Journal of Islamic Studies, 2024)
This study aims to analyzes the position of pesantren in the national education system based on Law No. 18 of 2019, focusing on Formal Diniyyah Education (PDF) and Mu’adalah Education. As religious-based institutions, pesantren play a strategic role in human resource development. The 2019 Pesantren Law grants them official recognition within the national education system. Using a qualitative descriptive-analytical approach, this study reviews policy documents, academic literature, and research reports. Findings show that the law provides a strong legal basis for pesantren, recognizing PDF and Mu’adalah as equivalent to formal education. However, challenges remain in accreditation, curriculum standardization, and institutional management. The study concludes that integrating pesantren into the national system is a progressive step, but stronger government support in regulation and funding is essential. Recommendations are given to policymakers and pesantren administrators to enhance the implementation of PDF and Mu’adalah in achieving national education goals.